2013
DOI: 10.1021/jm4014373
|View full text |Cite
|
Sign up to set email alerts
|

Novel S1P1 Receptor Agonists – Part 1: From Pyrazoles to Thiophenes

Abstract: From a high-throughput screening campaign aiming at the identification of novel S1P1 receptor agonists, the pyrazole derivative 2 emerged as a hit structure. Medicinal chemistry efforts focused not only on improving the potency of the compound but in particular also on resolving its inherent instability issue. This led to the discovery of novel bicyclo[3.1.0]hexane fused thiophene derivatives. Compounds with high affinity and selectivity for S1P1 efficiently reducing the blood lymphocyte count in the rat were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 78 publications
3
20
0
Order By: Relevance
“…Both S1PR1 and S1PR3 are expressed in the heart (Mazurais et al, 2002). Some studies suggested that S1PR3, and not S1PR1, mediates transient bradycardia in response to S1P (Forrest et al, 2004) and nonselective S1PR agonists (Forrest et al, 2004;Sanna et al, 2004); however, recent studies demonstrated that S1PR1 can also contribute to the bradycardia upon treatment with FTY720 (Murakami et al, 2010), with BAF312, a S1PR1,5 selective agonist (Fryer et al, 2012), and other S1PR1 agonists (Hamada et al, 2010;Bolli et al, 2013).…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 99%
“…Both S1PR1 and S1PR3 are expressed in the heart (Mazurais et al, 2002). Some studies suggested that S1PR3, and not S1PR1, mediates transient bradycardia in response to S1P (Forrest et al, 2004) and nonselective S1PR agonists (Forrest et al, 2004;Sanna et al, 2004); however, recent studies demonstrated that S1PR1 can also contribute to the bradycardia upon treatment with FTY720 (Murakami et al, 2010), with BAF312, a S1PR1,5 selective agonist (Fryer et al, 2012), and other S1PR1 agonists (Hamada et al, 2010;Bolli et al, 2013).…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 99%
“…65b In their quest for novel thiophene derivatives as immunosuppressive agents, Bolli and colleagues reported a relatively large scale (w18 g) trifluoromethylation of 3-iodo-N-methoxy-N,5,5-trimethyl-4,5,6,7-tetrahydrobenzo [c]thiophene-1-carboxamide with methyl chlorodifluoroacetate (2.4 equiv), CuI (1.6 equiv), and KF (1.6 equiv) in DMF at 134 C (Scheme 19). 66 Here, ClCF 2 CO 2 Me was added at 134 C over a period of 4 h to keep it at a low concentration and the corresponding trifluoromethyl product was obtained in 91% yield. The product was then converted to the targeted compound.…”
Section: Reactions Of Clcf 2 Co 2 Me With Heteroaryl Iodidesmentioning
confidence: 99%
“…Because of its special structure and bioactive activities, screening of structurally modified 3-carene derivatives for their bioactivity has received considerable attention. For instance, stable, potent, and selective sphingosine-1-phosphate receptor 1 (S1P 1 ) agonists were successively synthesized by using (+)-3-carene as starting material [ 11 ]. Ingenol and (+)-phorbol, two crucial natural products with various biological activities, especially anticancer, have been also synthesized from inexpensive (+)-3-carene [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%